Literature Review: Psychosocial Aspects as Determinants of Cancer Patients' Quality of Life - Umi Khudoifah; Herry Susanto; Ahmad Ikhlasul Amal; Suyanto Suyanto (Indonesian Journal of Global Health Research, 2025)
Cancer is a chronic disease that not only affects patients physically, but also causes significant psychosocial distress. These psychosocial aspects have been shown to reduce patients' quality of life, yet are often overlooked in clinical practice. In fact, psychosocial-based interventions can strengthen emotional resilience and improve overall therapeutic outcomes. This review aims to evaluate the contribution of psychosocial aspects to cancer patients' quality of life based on recent scientific literature. This study was a systematic literature review by searching articles from two major databases, namely PubMed and Google Scholar, within the period 2020-2025. The search strategy was organized based on the PICO framework using keywords such as “psychosocial factors”, “quality of life”, and “cancer patients”. From a total of 180 articles found, 28 duplicate articles were eliminated, leaving 152 unique articles. The next stage of screening was done by reviewing the titles and abstracts, so 79 irrelevant articles were excluded and 73 articles continued to the next stage. At the eligibility assessment stage, 32 articles were selected after full-text reading and evaluation based on the inclusion criteria, which included discussing the relationship between psychosocial aspects and the quality of life of cancer patients, being available in full-text format, and written in either English or Indonesian. Finally, an in-depth evaluation of the quality and relevance of the articles was conducted, resulting in only 10 articles being deemed eligible for analysis in this literature review. The literature review indicated that psychosocial aspects such as anxiety, depression, coping, social support, and spirituality were shown to determine the quality of life of cancer patients. Psychosocial aspects are important determinants of cancer patients' quality of life.